PENERAPAN PENCATATAN AKUNTANSI DALAM MENDUKUNG AKUNTABILITAS KEUANGAN PADA UMKM ANNISA 36, SEMARANG - Revy Amyneva Gulnoria; Khansa Shabihah; Rozihan Rozihan (Cermat : Jurnal Cendekiawan dan Riset Multidisiplin Akademik Terintegrasi, 2026)
This community service programme aimed to strengthen MSME financial accountability through simple accounting record-keeping assistance at Annisa 36 MSME in Semarang. The programme followed previous training on Electronic Data Capture (EDC), which had focused on non-cash transaction literacy. The assistance covered the separation of personal and business cash, the use of a cash book, routine transaction recording, and the documentation of digital transactions. The programme comprised an assessment of existing recording practices, material delivery, guided practice, and monitoring conducted one to two weeks after the activity. Data were analysed descriptively using four implementation indicators involving 36 participants. The monitoring results showed that all participants had separated personal and business cash. Twenty-eight participants (77.8%) used a cash book, while 26 participants (72.2%) routinely recorded transactions and documented digital transactions. These findings indicate that basic accounting practices had begun to be implemented, although recording consistency still required reinforcement. Follow-up assistance should focus on preparing simple income statements and periodically evaluating record-keeping practices.